Aplicações de visão computacional na indústria siderúrgica: problemas, soluções e estudos de caso - Turibio Tanus Salis (2008)
This work addresses the computer vision use in siderurgical (steel mill)process, from raw material extraction in the mines, passing for the reduction stages, stell plants, rolling, until finished products inspection. It shows a large survey where it describes the typical problems found by the researchers in the steel mill plants and the adopted solutions to solve them. This work still comments the development process of four computer vision aplications for the Ouro Branco mills siderurgical process and describes other solutions that can contribute in process quality increase.